Dynamics of wheel-soil systems : a soil stress and deformation-based approach - Pytka, Jaroslaw A. (Ground vehicle engineering series., 2013)
"Devoted to experimental methods of soil stress and deformation, as well as wheel forces determination and their use in wheel-soil system description, this book provides important knowledge of wheel-soil interaction that can be used for the modeling and simulation of wheels/tracks performance over soft ground. It offers novel ideas and designs of soil and snow pressure sensors, and optical-electronic system for soil deformation determination and wheel force transducers. It also describes field procedures and methods of sensor installation in soil/snow and the use of this equipment for both laboratory and field experiments"--